A Suitable Synthesis of 3,4-Dihydropyrimidin-2(1H)-ones/thiones by Microwave Irradiation - Pa Sha, M.A.; Jaya Shankara, V.P. (Asian Journal of Chemistry, 2016)
Zinc acetate dihydrate (Zn(OAc)2·2H2O) efficiently catalyzes the three-component coupling of b-keto ester, substituted aryl adehyde and urea or thiourea to afford the corresponding 3,4-dihydro-pyrimidin-2(1H)-ones/thiones respectively, the new protocol for the Biginelli reaction under microwave irradiation works in the absence of solvent. The yields are high and the reaction goes to completion within 40–60 sec.